2015
DOI: 10.1002/jmv.24378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of erythrovirus B19 infection in children with sickle cell disease: The impact of viral infection in acute clinical events

Abstract: B19V infection is common during childhood. It is self-limited in healthy individuals, but is often associated with transient aplastic crisis in children with sickle cell disease. The aim of this study was to estimate the prevalence and incidence of B19V infection in children with sickle cell disease screened by the Newborn Screening Program of Minas Gerais, Brazil, and followed-up at Fundação Hemominas. Serum or plasma samples from 278 patients were tested for anti-B19V IgG and IgM using commercial ELISA and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…It is known that the vast majority of children with SCA who have serologic evidence of previous B19V infection had not developed symptomatic aplastic crisis, 10 as was also demonstrated by our recent cohort study 5 . Different degrees of baseline hemoglobin concentration, virus load, virus genotypes or other unknown factors could explain this observation, although genotype and virus load were the same in both children during a nosocomial B19V outbreak, one child with very severe manifestations and the other with an asymptomatic course 11 .…”
Section: Commentssupporting
confidence: 77%
See 2 more Smart Citations
“…It is known that the vast majority of children with SCA who have serologic evidence of previous B19V infection had not developed symptomatic aplastic crisis, 10 as was also demonstrated by our recent cohort study 5 . Different degrees of baseline hemoglobin concentration, virus load, virus genotypes or other unknown factors could explain this observation, although genotype and virus load were the same in both children during a nosocomial B19V outbreak, one child with very severe manifestations and the other with an asymptomatic course 11 .…”
Section: Commentssupporting
confidence: 77%
“…In a study of 278 children with sickle cell disease (SS or Sβ 0 -thalassemia, median age 5.8 years; range: 0.9–12.3 years), it has been shown that past or recent viral infection occurred in 29.5% (95% confidence interval: 24.1–34.9%) 5 . This report describes the clinical course and the laboratory tests of two siblings selected to participate in that cohort.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The specific rate is unclear; therefore, risk was estimated for three values: 1%, 5%, and 10%. The number of red blood cells (RBCs) transfused to patients with hereditary hemolytic anemias (HHAs) per year is approximately equal to national hospital separations for these conditions with equivalent RBC use patterns to those reported in a 2011 South Australian study Transfusion‐dependent and sporadically transfused sickle cell disease (SCD) patients receive an average of 20 and 2 RBC components per year, respectively. The frequency of B19V‐attributable transient aplastic crisis (TAC) in patients with SCD is 40%, which is applicable to patients with other HHAs. …”
Section: Methodsmentioning
confidence: 99%
“…Owing to the long life span of erythrocytes, the clinical effect is usually minimal in immunocompetent individuals, although anemia and/or other cytopenias may occur . However, where there is preexisting high red cell turnover, increased hematopoietic demand, and/or impaired immunity, infection may be severe (Table ) . B19V infection may be associated with a wide range of other symptoms and clinical manifestations in immunocompetent individuals including encephalitis and cardiac diseases such as myocarditis …”
Section: Effect Of Parvovirus B19 Infection In Nonimmune Vulnerable Gmentioning
confidence: 99%